Peran Guru Pendidikan Agama Islam Dalam Meningkatkan Karakter Islami Peserta Didik Di Smk Negeri 2 Rangkasbitung - Arissalman Alfarisi; Pupu Mahpudin; Mochamad Husen (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2026)
Islamic Religious Education teachers play a crucial role in shaping students’ character at school. This is because Islamic Religious Education teachers are the ones who can guide students’ character development in accordance with Islamic law. The role of these teachers is to transform students with previously poor character into those with good character, and to help those who already have good character become even better. The objective of this study is to examine the role of Islamic Religious Education teachers in enhancing students’ Islamic character at SMK Negeri 2 Rangkasbitung. This study employed a descriptive qualitative method, utilizing data collection instruments such as observation, interviews, and documentation. To validate the data, the researcher employed source triangulation, technique triangulation, and time triangulation. The results of the study indicate that the role played by Islamic Religious Education teachers in enhancing the Islamic character of 12th-grade students The APHP 3 program at SMK Negeri 2 Rangkasbitung has been rated as good, as the Islamic Religious Education teachers have taught and guided students to exhibit good character. The efforts made by the Islamic Religious Education teachers to foster Islamic character include serving as motivators, educators, and surrogate parents, as facilitators, as mentors using the exemplary method and the habituation method, which emphasize the values of Hablum minaallah, Hablum minannas, Hablum minal alam, and self-discipline. Meanwhile, the factors that support the development of students’ Islamic character are external factors—that is, factors influenced by external sources such as the family—while the factors that hinder the development of Islamic character include peer influence that encourages negative behavior and excessive use of social media.